2006
DOI: 10.1530/rep.1.01015
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed expression of genes involved in transcription and translation in in vitro compared with in vivo cultured bovine embryos

Abstract: In vivo-derived bovine embryos are of higher quality than those derived in vitro. Many of the differences in quality can be related to culture environment-induced changes in mRNA abundance. The aim of this study was to identify a range of mRNA transcripts that are differentially expressed between bovine blastocysts derived from in vitro versus in vivo culture. Microarray (BOTL5) comparison between in vivo-and in vitro-cultured bovine blastocysts identified 384 genes and expressed sequence tags (ESTs) that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 60 publications
2
71
2
1
Order By: Relevance
“…We both confirmed previously detected transcripts such as IGF2R and DNMT1 and identified previously uncharacterized transcripts such as regulator of chromatin-structure SWI/ SNF and NFYA at the 8-cell stage (Table 2). In vitro-produced bovine blastocysts are known to have different mRNA expression patterns as compared with their in vivo-derived counterparts (14,15). Although lower than in vivo-derived blastocysts, reasonable pregnancy and calving rates (35-45%) have been obtained by using in vitro-derived bovine blastocysts (7,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We both confirmed previously detected transcripts such as IGF2R and DNMT1 and identified previously uncharacterized transcripts such as regulator of chromatin-structure SWI/ SNF and NFYA at the 8-cell stage (Table 2). In vitro-produced bovine blastocysts are known to have different mRNA expression patterns as compared with their in vivo-derived counterparts (14,15). Although lower than in vivo-derived blastocysts, reasonable pregnancy and calving rates (35-45%) have been obtained by using in vitro-derived bovine blastocysts (7,15).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro-produced bovine blastocysts are known to have different mRNA expression patterns as compared with their in vivo-derived counterparts (14,15). Although lower than in vivo-derived blastocysts, reasonable pregnancy and calving rates (35-45%) have been obtained by using in vitro-derived bovine blastocysts (7,15). It might be that the in vitro-cultured embryos express different transcripts to deal with the suboptimal culture conditions and that the expression profiles do not necessarily indicate their abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulated genes in NT embryos were suggested to compromise membrane formation (nidogen 2) and increase maternal immune responses to over-expressed MHC-I genes. Corcoran et al (2006) identified differences in gene expression profiles between bovine blastocysts derived from in vivo v. in vitro. Of the 384 genes and expressed sequence tags that were differentially expressed, 85% were down-regulated in the latter.…”
Section: Recent Transcriptomic Studies On Dairy Cow Fertilitymentioning
confidence: 99%
“…Of the 384 genes and expressed sequence tags that were differentially expressed, 85% were down-regulated in the latter. The inferior quality of in vitroderived embryos was associated with a decreased level of gene expression and, possibly, caused by a deficiency of the machinery associated with transcription and translation (Corcoran et al, 2006). Gene expression profiles can be used to define normal and deviant embryos and from here optimize embryo production protocols.…”
Section: Recent Transcriptomic Studies On Dairy Cow Fertilitymentioning
confidence: 99%
“…Several major developmental events occur during this period, including the first cleavage division, the timing of which is important in determining subsequent embryo development; embryonic genome activation and morula compaction which involves establishment of the first intimate cell-to-cell contact in the embryo and blastocyst formation involving differentiation of two cell types, the trophectoderm and inner cell mass (Bavister 1995;Lonergan et al 1999). Many of the differences in embryo quality can be attributed to culture environment medium-induced changes in mRNA abundance (Wrenzycki et al 1996;Corcoran et al 2006). Studies on the embryonic genome indicate that currently used in vitro embryo development conditions cannot fully mimic in vivo conditions with regard to mRNA expression.…”
Section: Introductionmentioning
confidence: 99%